2016
DOI: 10.1016/j.jvs.2016.06.096
|View full text |Cite
|
Sign up to set email alerts
|

Amputation trends for patients with lower extremity ulcers due to diabetes and peripheral artery disease using statewide data

Abstract: Objective This study reports all-payer amputation rates using state-based administrative claims data for high-risk patients with lower extremity (LE) ulcers and concomitant peripheral artery disease (PAD), diabetes mellitus (DM), or combination PAD/DM. In addition, we characterize patient factors that affect amputation-free survival. We also attempted to create a measure of a patient’s ability to manage chronic diseases or to access appropriate outpatient care for ulcer management by accounting for hospital an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 26 publications
3
34
0
1
Order By: Relevance
“…CLI patients with diabetes are at average 3 years younger compared to non-diabetic patients at the same Rutherford grade. This trend conforms with other studies [11, 21], and likely reflects the progressing effect of diabetes on the arterial calcification and clinical severity of PAD. Further, diabetic CLI patients are shown higher ratio of obesity, dyslipidemia, or hypertension as common co-morbidities (“metabolic syndrome”), as well as higher ratio of chronic kidney disease or coronary artery disease as common sequelae of diabetes [22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…CLI patients with diabetes are at average 3 years younger compared to non-diabetic patients at the same Rutherford grade. This trend conforms with other studies [11, 21], and likely reflects the progressing effect of diabetes on the arterial calcification and clinical severity of PAD. Further, diabetic CLI patients are shown higher ratio of obesity, dyslipidemia, or hypertension as common co-morbidities (“metabolic syndrome”), as well as higher ratio of chronic kidney disease or coronary artery disease as common sequelae of diabetes [22].…”
Section: Discussionsupporting
confidence: 92%
“…It may be concluded, that end-stage PAD patients with tissue loss have such poor prognosis in terms of survival (50–60% at 4 years), that concomitant diabetes itself would not relevantly further increase mortality rates. This finding is paralleled by Humphries et al [21] that did not show any further deteriorating effect of diabetes on in-hospital mortality of PAD patients with lower extremity ulcers on statewide data for California, USA. In face of the recent nationwide study by Agarwal et al [34] the more frequently used endovascular treatment strategy in the diabetic sub-group might add to the improved survival.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Contemporary studies have shown a decline in amputation rates for Medicare beneficiaries with PAD in general and across racial subgroups, although disparities still exist 3, 38. Multidisciplinary preventative measures such as diabetic control and wound care, along with patient and community engagement, seem to decrease racial disparity in limb loss among diabetic patients and may hold promise in PAD care 12, 38, 39. Increased awareness and education of providers in reducing implicit bias in the treatment of PAD is also needed 40.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have argued that race could be a marker for socioeconomic status (SES) and thus for healthcare access, as the reason for racial disparity in vascular outcomes 11, 12, 13. Lack of access to care and regional clustering have been shown to affect black patients disproportionately 3, 7.…”
mentioning
confidence: 99%